Oral Modeling of an Adenovirus-Based Quadrivalent Influenza Vaccine in Ferrets and Mice. Issue 2 (June 2016) - Scallan, Ciaran; Lindbloom, Jonathan; Tucker, Sean
Abstract Introduction Oral vaccines delivered as tablets offer a number of advantages over traditional parenteral-based vaccines including the ease of delivery, lack of needles, no need for trained medical personnel, and the ability to formulate into temperature-stable tablets. We have been evaluating an oral vaccine platform based on recombinant adenoviral vectors for the purpose of creating a prophylactic vaccine to prevent influenza, and have demonstrated vaccine efficacy in animal models and substantial immunogenicity in humans. These studies have evaluated monovalent vaccines to date. To protect against the major circulating A and B influenza strains, a multivalent influenza vaccine will be required. Methods In this study, the immunogenicity of orally delivered monovalent, bivalent, trivalent, and quadrivalent vaccines was tested in ferrets and mice. The various vaccine combinations were tested by blending monovalent recombinant adenovirus vaccines, each expressing hemagglutinin from a single strain. Human tablet delivery was modeled in animals by oral gavage in mice and by endoscopic delivery in ferrets. Results We demonstrated minimal interference between the various vaccine vectors when used in combination and that the oral quadrivalent vaccine compared favorably to an approved trivalent inactivated vaccine. Conclusion The quadrivalent vaccine presented here produced immune responses that we predict should be capable of providing protection against multiple influenza strains, and the platform should have applications to other multivalent vaccines. Funding Vaxart, Inc.